Estágio supervisionado em Filosofia: contribuições para a formação inicial de professores - Melo, Elizabete Amorim de Almeida (2019)
This research aims to contribute to the construction of the history of the formation of Philosophy teachers in Alagoas, considering, as theoretical and methodological cut, the work developed on the Supervised Internship in Philosophy 1, 2, 3 and 4 subjects of the Federal University of Alagoas (UFAL) between 2010 and 2014. Thus, this doctoral work brings the following research questions: How do the Supervised Internship in Philosophy 1, 2, 3 and 4 subjects fit in the pedagogical project of the Philosophy course? How do these subjects contribute to the training of the students graduated in Philosophy from UFAL? We present two kinds of work (didactic and academic/scientific) developed by students on the given period: the class planning for Teaching Philosophy on high school based on the "Melo Methodology" (MELO, 2014a; 2013a) – didactic production – and the mapping of term papers, abstracts and papers published in national and international scientific events on the given period – academic/scientific production (MELO et al, 2014). This research does not intend to be only a report, but to be a reflection-action over the pedagogical and educational theory and practice for possible changes in the formation of future teachers (FREIRE, 1996; MORIN, 2005; 2002) in Philosophy (LIMA et al, 2019; MELO, 2014a; 2013a; MATOS, 2013), beyond the prescription of official documents. Among the data collected during the research, we highlight: the Supervised Internship in Philosophy subjects occupy a non-place in the official curriculum of the UFAL Philosophy course. Nevertheless, through the actions of the educational subjects (teacher/advisor and students) they resist and insist, effectively contributing to the formation of undergraduates, whether in the construction and planning of over two hundred and fifty (250) lectures for the Teaching of Philosophy for basic education, using the Melo Methodology; or in the academic production of more than fifty (50) papers and seventeen (17) term papers about the Teaching of Philosophy.